“RETOS QUE AFRONTA EL MERCADO MARÍTIMO ECUATORIANO EN CONSECUENCIA A LA CRISIS ECONÓMICA DEL 2008” - Morales Velarde, Carlos Eduardo (2014)
The economic crisis of 2008 generated global losses in all sectors, the maritime sector is no exception and triggering problems in transportation between the different 3 countries involved. The objective of this research is to measure the effects it has had the economic crisis of 2008 in the Ecuadorian maritime sector and in turn know the alternatives to address this situation. Through surveys of perception of the different actors in the maritime sector, attempts to quantify the factors that have led to a decline in this activity considering that the cargo container is the most used nowadays. The results show that a small decrease in transport was obtained by factors such as increased port charges and problems of funding to develop the shipping business. Finally, you need to opt for technological resources that help improve the logistics of this service for years have been fundamental to the development of the country.